Australia's Amazing Kangaroos : Their Conservation, Unique Biology, and Coexistence With Humans - Richardson, Ken, 1947- (Australia CSIRO Publishing, 2012)
Provides an authoritative source of information and insight into the world of this intriguing marsupial.
Include Illustration, Table, Appendix and Index
Keywords: Australia -- Kangaroos -- Wildlife conservation